Preface: 4th International Symposium on Economics, Management, and Sustainable Development (EMSD 2023) - Karsten, Sandy; Liu, Qing (Transactions on Economics, Business and Management Research, 2024)
The volume is the collection of papers presented as the 4th International Symposium on Economics, Management, and Sustainable Development (EMSD 2023), which was held on December 30-31, 2023 in Hangzhou City, China. It was co-organized by Suzhou Branch of Zewang Investment Co., Ltd. and Hubei Yanxue Boke Cultural Communication Co., Ltd.The aim of EMSD 2023 is to provide a platform for accountants, financial industry practitioners, scholars, managers and graduate students from different cultural backgrounds to present and discuss research, developments and innovations in all fields of Economics, Management, and Sustainable Development. It provides opportunities for the delegates to exchange new ideas and application experiences, to establish business or research relations and to find global partners for future collaboration.All full paper submissions to the EMSD 2023 could ONLY be written in English, and will be sent to 2-3 reviewers and evaluated based on originality, technical or research content or depth, correctness, relevance to conference, contributions, and readability. EMSD 2023 received 71 manuscripts. And 27 submissions had been accepted by our reviewers. The Committees of EMSD 2023 invested great efforts in reviewing the papers submitted to the conference and organizing the sessions to enable the participants to gain maximum benefit.Conference Organizing Committees